Reconciling observations of global temperature change (Compass series (Washington, D.C.), 2000)
The National Academy Press presents the full text of "Reconciling Observations of Global Temperature Change," a book originally published in Washington, D.C., in 2000 by the Commission on Geosciences, Environment and Resources of the National Research Council. The report focuses on an assessment of apparently conflicting global surface and upper air temperature trends and on the identification of the reasons for the differences.